2019
DOI: 10.1136/tobaccocontrol-2019-054952
|View full text |Cite
|
Sign up to set email alerts
|

JUUL use and reasons for initiation among adult tobacco users

Abstract: BackgroundThe electronic nicotine delivery system (ENDS) JUUL has quickly captured the ENDS market, representing 74.6% of the total dollar share for this category as of November 2018. Although JUUL is marketed as an alternative to cigarettes intended for current adult smokers, evidence suggests that a majority of ENDS users are concurrently current cigarette smokers. Little is known about the dual use of JUUL and cigarettes, as well as the reasons for trying JUUL among adult tobacco users.MethodsA survey field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
2
27
1
Order By: Relevance
“…This finding seems incongruent with JUUL’s stated mission of improving the lives of smokers by eliminating combustible cigarette use and replacing it with the — purportedly less harmful — JUUL product [ 46 ]. This observation is also inconsistent with the results of a 2019 survey reporting that around 20% of individuals aged 18-24 years initiated JUUL use in an attempt to quit combustible tobacco [ 47 ]. Additional research has suggested that youth not only appear to be experimenting with JUUL but are also habitually using the device [ 48 ].…”
Section: Discussioncontrasting
confidence: 59%
“…This finding seems incongruent with JUUL’s stated mission of improving the lives of smokers by eliminating combustible cigarette use and replacing it with the — purportedly less harmful — JUUL product [ 46 ]. This observation is also inconsistent with the results of a 2019 survey reporting that around 20% of individuals aged 18-24 years initiated JUUL use in an attempt to quit combustible tobacco [ 47 ]. Additional research has suggested that youth not only appear to be experimenting with JUUL but are also habitually using the device [ 48 ].…”
Section: Discussioncontrasting
confidence: 59%
“…First, the study relied on an online sample that may be subject to selection bias; for example, the respondents who participated in online studies may hold certain characteristics that put them at different risks of using JUUL compared to the general population. However, the prevalence of ever and current JUUL use among adult smokers in our study is comparable to that of a nationally representative study [5] and an online study using a large U.S. sample of adult combustible users [6], signifying that our data may resemble the pattern of using JUUL among adult smokers in the U.S. Nevertheless, our findings need to be further confirmed with studies using large samples.…”
Section: Plos Onesupporting
confidence: 78%
“…Among smokers aged 15-34, 14% and 10% had ever used JUUL and used JUUL in the past 30 days, respectively [5]. Another recent study found that in 2018, among adult combustible tobacco users aged 18-54 in the U.S., 15% and 12% had ever used JUUL and used JUUL in the past 30 days, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Young adults are a priority population for tobacco control. 9,18,22,54 The present study adds to the literature one of the first studies of JUUL cessation-related perceptions and behaviors. Nearly half of college student JUUL users had deliberately tried to quit.…”
Section: Discussionmentioning
confidence: 75%